2020
DOI: 10.1142/s179398442040005x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Nucleic Acid Tests Are Necessary for Early Diagnosis of Atypical COVID-19: A Case Report

Abstract: In Wuhan, China, the first case of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was reported on December 8, 2019. The patient’s symptoms included fever, coughing and breathing difficulties. According to the sixth China version of 2019 coronavirus disease (COVID-19) diagnostic criteria, some patients with COVID-19 may present atypical symptoms and have negative nucleic acid tests (NATs), possibly leading to misdiagnosis and viral transmission. Our patient was a 29-year-old woman who complained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…During the initial period of the COVID‐19 outbreak in the first quarter of 2020, the public understandings on the key functions of the masks were quite limited without much of the first‐hand COVID‐related experimental data at the time. Some media even suggested that it was not necessary to wear masks in public (Public Health Experts Keep Changing Their Guidance on Whether or Not to Wear Face Masks for Coronavirus; WHO, 2020). Both inconsistent explanations and the shortage of commercial masks may have contributed to such public opinion.…”
Section: Function Of Masks In Respiratory Epidemicmentioning
confidence: 99%
See 1 more Smart Citation
“…During the initial period of the COVID‐19 outbreak in the first quarter of 2020, the public understandings on the key functions of the masks were quite limited without much of the first‐hand COVID‐related experimental data at the time. Some media even suggested that it was not necessary to wear masks in public (Public Health Experts Keep Changing Their Guidance on Whether or Not to Wear Face Masks for Coronavirus; WHO, 2020). Both inconsistent explanations and the shortage of commercial masks may have contributed to such public opinion.…”
Section: Function Of Masks In Respiratory Epidemicmentioning
confidence: 99%
“…Without the specific therapeutics and vaccines, the key to stop the spreading of COVID‐19 has to be dependent on preventative precautions by all means possible among which social distancing and quarantine have not only been recommended but also mandated by various state and federal regulations especially for those who have been infected (CDC, 2019, 2020; Parmet & Sinha, 2020). However, the asymptomatic carriers and misdiagnosis in nucleic acid tests make it more difficult to isolate the patients, therefore increasing the risks of virus spreading (Bai et al, 2020; Qu et al, 2020). Thus, the physical protection for individuals is necessary to kerb virus transmission, and one common and widely used method is wearing of masks.…”
Section: Introductionmentioning
confidence: 99%